Instituições de ensino superior e as redes sociais da internet: um panorama atual no Brasil sobre a atuação das IES nos sites Facebook e Twitter - Oliveira, Wellington Gabriel Freitas de (2012)
Given the popularity of social networks on the internet all around the world and the advantages and disadvantages of cyberculture, the Internet presents itself to higher education institutions (HEI’s) as a favorable means to marketing activities aiming the competitiveness improvement. Concerning to the social networks on the Internet and its feature of conversational and informational activities, such spaces have become one of the major technological and social tools of the current era. As these spaces theoretically are an opportunity for brand exposure and relationship with customers, in this issue it was questioned how the Brazilian higher education institutions operate in social networks. Considering that, this paper conducted a study organized in two phases. The first consists in a census with all Brazillian HEI’s and the second is an in-depth analysis with multiple cases involving the five highest score HEI’s in the country on General Index of Courses (GIC). In the census, were searched institutional and registry information about all HEI’s, population rates, Gross Domestic Product (GDP) of Brazilian regions and features of HEI’s performance on the websites Twitter and Facebook. In the analysis into depth, they were observed features of published content, public contact with associated users, parallel applications programs used and divulgation by the HEI’s. It was seen in this study that 50,5% of HEI’s in the country are registered in social networking sites, but only 33% of Brazilian HEI’s maintain themselves active on Facebook and only 41% on Twitter. It was seen also that the Southeast is the region that has more active HEI’s on social networking sites, but also that is the South region that maintains the best performance in percentage of active HEI’s. It was also possible to realize that the five best HEI’s in GIC are not necessarily public universities nor work actively on social networking sites, even if this condition appears when analyzed the five best HEI’s in GIC inside each region. It was finally concluded that Brazillian HEI’s currently are not following the global trends concerning to social networks on the internet, once that it is not observed an adhesion in large-scale, but with growth prospects in the forthcoming GIC report.